PERANAN KAPTEN ZAINAL ZEN SEBAGAI TOKOH PEJUANG DALAM PEMBEBASAN IRIAN BARAT DARI PENJAJAHAN BELANDA TAHUN 1961-1963 - Adelin Nandisa; Isjoni Isjoni; Asyrul Fikri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Captain Zainal Zen is a military figure in the Indonesian Army, Indonesian Army during the liberation of West Irian in 1961-1963. Zainal Zen was born in Parit Putuih, August 11, 1962 by parents named Saelan and Muhammad Zen St. Kayo. Zainal Zen is an only child and plays a role in the liberation of West Irian from Dutch colonialism. The aim of this study is to find out the background of Zainal Zen's life, to determine Zainal Zen's role as a warrior in the liberation of West Irian from Dutch colonialism in 1961-1963 and to find out what distinctions Zainal Zen received from the government, and to find out the end of the battle from Zainal Zen. The data analysis used the historical writing method that consisted of several stages, namely heuristics, verification, interpretation and historiography. The result of this investigation is that Zainal Zen received special military training in Danton Kesehatan. Zainal Zen carried out the trichora operation in 1961 as part of the liberation of West Irian. He was appointed Platoon Commander (Dan Ton) for Health Jon Arsu-3, where he was instrumental in providing basic training in proper and correct treatment and medication techniques according to common medical procedures. Training in medical care and medical treatment techniques is an activity that must be mastered by the combat unit health team to provide assistance to fellow colleagues, both in the unit, especially when faced with the battlefield. Zainal Zen has seven members of the health team. After the end of operations, Zainal Zen was stationed in the Pekanbaru area. When he retired, Zainal Zen joined the Veterans Legion Organization of the Republic of Indonesia. Zainal Zen received many awards from the government. Key Words: Role, Zainal Zen, Liberation of West Irian, Dutch colonialism.